Treatment of Sclerosing Mesenteritis with Corticosteroids and Azathioprine - Anand Bala; Sylvain P Coderre; Douglas RE Johnson; V Nayak (Canadian Journal of Gastroenterology)
Sclerosing (idiopathic) mesenteritis is a rare disease that may present with abdominal pain or bowel obstruction. A 21-year-old man was diagnosed with sclerosing mesenteritis, and treated with a partial ileal resection and defunctioning ileostomy. He was subsequently started on corticosteroids and azathioprine. Five months later, at the time of ileostomy reversal, he was disease-free. The diagnosis and management of this disease are discussed.